Jaringan Informasi dan Legitimasi Kekuasaan dalam Film Dokumenter Pesta Babi: Analisis Perspektif Nexus Yuval Noah Harari - Fachri Syauqii; Azis Batubara (Communication & Social Media, 2025)
This study aims to analyze the representation of contemporary colonialism in the documentary film Pesta Babi: Colonialism in Our Time by Dandhy Laksono and to explain how information networks shape the legitimacy of power within the context of Papuan politics through the Nexus perspective proposed by Yuval Noah Harari. The research employs a qualitative approach using Norman Fairclough’s Critical Discourse Analysis method. The primary data were obtained from the documentary film Pesta Babi: Colonialism in Our Time, while supporting data were drawn from the book Nexus: A Brief History of Information Networks from the Stone Age to AI, scholarly articles, and other relevant literature. The analysis focuses on narratives, dialogues, visuals, and social representations related to development, security, Indigenous communities, and the exploitation of natural resources in Papua. The findings reveal that the film represents Papua as a contested space where national development interests, extractive economic expansion, and the survival of Indigenous communities intersect. The study further demonstrates that the legitimacy of state policies is constructed through information networks that produce narratives of development, security, and national integration. Pesta Babi presents an alternative narrative that exposes the impacts of militarization, environmental degradation, and the marginalization of local communities, illustrating that contemporary colonialism operates through the control of natural resources, living spaces, and information production.